2021
DOI: 10.1037/ppm0000339
|View full text |Cite
|
Sign up to set email alerts
|

Are there two types of escapism? Exploring a dualistic model of escapism in digital gaming and online streaming.

Abstract: Escapism is predominantly assumed to be a negative aspect of media consumption. However, research also indicates that escapism may spur positive psychological outcomes. Here, using a 2-dimensional model of escapism and its corresponding scale, we tested a dualistic approach to escapism in relation to both gaming and online streaming. Data were collected from 2 separate Web-based questionnaires. Study 1 comprised 126 dedicated gamers, whereas Study 2 comprised 191 university students regularly using streaming s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 55 publications
5
32
0
2
Order By: Relevance
“…Conceptually, this is consistent with the previous findings where gaming for mood management also occurs in non-problematic play (Lemmens et al, 2015;Rehbein et al, 2015). Although recent literature (Stenseng et al, 2021) has suggested different operationalizations to reflect different kinds of escape and only those involving "self-suppression" to be IGD-relevant, in our data escape was weak and non-influential despite self-suppressive operationalization-thus yielding counterevidence for the above. Notably, the ICD-11 does not list any mood management as a criterion for GD.…”
Section: Rq 11 Symptoms In the Networksupporting
confidence: 90%
“…Conceptually, this is consistent with the previous findings where gaming for mood management also occurs in non-problematic play (Lemmens et al, 2015;Rehbein et al, 2015). Although recent literature (Stenseng et al, 2021) has suggested different operationalizations to reflect different kinds of escape and only those involving "self-suppression" to be IGD-relevant, in our data escape was weak and non-influential despite self-suppressive operationalization-thus yielding counterevidence for the above. Notably, the ICD-11 does not list any mood management as a criterion for GD.…”
Section: Rq 11 Symptoms In the Networksupporting
confidence: 90%
“…(2014) consensus statement on IGD criteria; PGQ = Problematic gaming questionnaire, 22-item adapted from gambling ( Gentile, 2009 ; Charlton, 2002 ); PIU = Problematic Internet Use scale (PIU) ( Chen, Lo, & Lin, 2015 ); POGQ-18 = Problematic Online Gaming Questionnaire (Demetrovics et al, 2012) ; POGQ-12 = Problematic Online Gaming Questionnaire ( Pápay et al, 2013 ); POGUS = Problematic Online Gaming Use Scale ( Kim & Kim, 2010 ); PVGT = Problem Video Game Playing Test ( King et al, 2011 ); PVP = Problem Video Game Playing Questionnaire ( Salguero & Morán, 2002 ); YDQ-8 = Young Diagnostic Questionnaire - 8 item ( Young, 1998b ); YIAT-WoW Internet Addiction Test – World of Warcraft version ( Young, 1998a ; Khazaal et al, 2008 ; Billieux et al., 2013 ). ES = the Escapism Scale ( Stenseng et al, 2021 ); EGMQ = Electronic Gaming Motives Questionnaire ( Myrseth et al., 2017 ); GAMES = The gaming attitudes, motives, and experiences scales ( Hilgard et al., 2013 ); GAMS = Gaming Motivations Scale ( Lafrenière et al., 2012 ); MOGQ = The Motives for Online Gaming Questionnaire ( Demetrovics et al., 2011 ); MOGQ-14 = Motives for Online Gaming Questionnaire -14 ( Demetrovics et al., 2011 ; Kircaburun et al., 2018 ); MPOGQ = Motivations for Play in Online Games ( Yee, 2006a ); MPOGQ-WoW = Motivations for Play in Online Games adapted to World of Warcraft ( Billieux et al., 2013 ; Yee, 2006b ); MPOGQ-10 = Motivations for Play in Online Games ( Williams et al., 2008 ); NE = The Negative escapism scale ( Hagström & Kaldo, 2014 ); OGMS = Online Gaming Motivations Scale ( Yee et al., 2012 ); PENS = Player Experience of Need Satisfaction ( Ryan et al., 2006 ); VMQ = Videogaming Motives Questionnaire ( López-Fernández et al., 2020 ). US = United States, CA = Canada, BR = Brazil, PE = Peru, UK = United Kingdom, GE= Germany, NE = Netherlands, FI = Finland, PL = Poland, FR= France, IT = Italy, SE = Sweden, RO = Romania, AT = Austria, CZ = Czechia, PT = Portugal, DK = Denmark, GR = Greece, HU = Hungary, NO = Norway, ES = Spain, BE = Belgium, LV = Latvia, RU = Russia, CH = Switzerland, HR = Croatia, LT = Lithuania, LU = Luxembourg, MT = Malta, RS = Serbia, SK = Slovakia, SI = Slovenia, TR = Turkey, NG = Nigeria, SG = Singapore, IN = India, KR = South Korea, HK = Hong Kong, ID = Indonesia, IQ = Iraq, IL = Israel, JP = Japan, TH = Thailand, AE = United Arab Emirates, AU = Australia, NZ = New Zealand and PH = Philippines (the).…”
Section: Resultsmentioning
confidence: 99%
“…ES 5 the Escapism Scale (Stenseng et al, 2021); EGMQ 5 Electronic Gaming Motives Questionnaire (Myrseth et al, 2017); GAMES 5…”
Section: Problemmentioning
confidence: 99%
“…Moreover, “escapist” gaming may act as a coping strategy for dealing with real‐life difficulties, this was associated with more problematic outcomes (Stetina et al, 2011). However, and more recently, studies are starting to indicate that escapism may spur positive psychological outcomes (Li et al, 2015; Stenseng et al, 2021). For instance, the increase of mobile, portable handheld consoles coupled with AR games are known to provide ease of access which gives players convenience of playing the game anywhere and at any time, thus reinforcing escapism (Ghazali et al, 2019; Laor, 2020) as a means to de‐stress or distract themselves unpleasant situations and negative mood states (Nordby et al, 2019).…”
Section: Thematic Analysis Of Motivationsmentioning
confidence: 99%